Fearful symmetry in aposematic plants - Lev-Yadun, Simcha (Landes Bioscience, 2011)
Symmetry has been proposed to increase the efficiency of visual aposematic displays in animals, and I suggest that it may also be true for many aposematic spiny or poisonous plants. For instance, in the very spiny plant taxa cacti, Aloe sp., Agave sp. and Euphorbia sp., which have been proposed to be aposematic because of their colorful spine system, the shoots, and in cacti, the spiny fruits as well, are usually radially symmetric. Moreover, in the radial symmetric shoots of Agave and Aloe their individual spiny leaves are also bilaterally symmetric. Spiny or poisonous fruits of various other taxa, the symmetric spiny leaf rosettes and flowering spiny heads of many Near Eastern species of the Asteraceae and other taxa, and poisonous colorful flowers in taxa that were proposed to be aposematic are also symmetric. Thus, in plants, like in animals, symmetry seems to be commonly associated with visual aposematism and probably contributes to its effectiveness. Symmetry may stem from developmental constraints, or like in flowers, have other signaling functions. However, because of the better perception of symmetry by animals it may exploit inherited modes of animal sensing that probably result in paying more attention to symmetric shapes. All these possible alternatives do not negate the probable deterring role of symmetry in plant aposematism.